In‐house validation and application of UHPLC‐MS/MS method for the quantification of pyrrolizidine and tropane alkaloids in commercial honey bee‐collected pollen, teas and herbal infusions purchased on Italian market in 2019–2020 referring to recent European Union regulations. (30th January 2022) - Martinello, Marianna; Manzinello, Chiara; Gallina, Albino; Mutinelli, Franco
Summary: Two analytical methods for the quantification of pyrrolizidine (PAs) and tropane alkaloids (TAs) in honey bee‐collected pollen, teas and herbal infusions have been in‐house validated using the UHPLC‐MS/MS technique. These methods showed good linearity, good accuracy and robustness. The methods have been applied to a preliminary investigation of forty‐seven pollen samples and thirty‐three packs of tea‐bags in light of Commission Regulations (EU) 2020/2040 and 2021/1408 regarding maximum limits of PAs and TAs in foodstuffs, respectively. About half of the pollen samples contained searched PAs but in concentrations significantly lower than the maximum limit established; two samples were contaminated with TAs. One third of teas or herbal infusions contained PAs or TAs, one sample exceeded the EU limits for PAs and one for TAs. Despite the final consumer's health does not seem threatened, these results recommend accurate analytical methods and broader investigations for PAs and TAs in foods. Abstract : Two methods for the quantification of pyrrolizidine (PAs) and tropane alkaloids (TAs) in honey bee‐collected pollen, teas and herbal infusions have been validated using the UHPLC‐MS/MS technique and applied to these matrices. The results were evaluated in light of Commission Regulations (EU) 2020/2040 and 2021/1408 regarding maximum limits of PAs and TAs in foodstuffs.